Double-edged cohesion: Multidimensional impacts of community governance's cohesion in community-driven development. Issue 4 (8th August 2021) - Kim, Booyuel; Lee, Junesoo; Chung, Jongwoo
ABSTRACT: While often pursued as a desirable state for a society or community, group cohesion can be a double-edged sword. When it comes to Community-Driven Development (CDD), in which community members are expected to collaborate to ensure their co-prosperity, group cohesion would be a matter of not only "WHETHER or not it is needed" but also "WHEN/WHERE/HOW MUCH it is needed". This study examines a rural CDD case implemented by the Korea International Cooperation Agency (KOICA) and the Myanmar Ministry of Agriculture, Livestock and Irrigation (MOALI). The analyses imply some common patterns of village cohesion for successful CDD performance: complementary communication roles shared by multiple leaders; the coexistence of physical and mental preparedness; balance between optimistic and realistic prospects; a long-term horizon for planning and implementation; introspective attribution of challenges; and constructive divergences and coordination in goal setting. We conclude with theoretical and practical conditions of multi-dimensionally balanced group cohesion in community development.